Carbon dioxide adsorption studies on delafossite CuFeO2 hydrothermally synthesized. (November 2016) - Sarabia, M.A.; Rojas, S.D.; López-Cabaña, Z.; Villalba, R.; González, G.; Cabrera, A.L.
Abstract: Delafossite CuFeO2 oxide was synthesized by a hydrothermal technique using Cu2 O and FeOOH as precursors with the addition of fused NaOH as mineralizer. The amount of rhombohedral and hexagonal delafossite phase formed depends on the synthesis time lapses between 2 and 5 days and on the NaOH concentration. The compounds obtained were analyzed with Raman Spectroscopy, X-Ray Diffraction (XRD), X-Ray Photoelectron Spectroscopy (XPS), Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) in order to obtain their morphological and structural properties. Optical behavior was studied by UV–vis Spectroscopy and gas adsorption measured with a Quartz-Crystal Microbalance (QCM). Our results show that this type of hydrothermal synthesis is capable of recreating the delafossite-type structure of copper-iron oxide and produces a high yield of material with the right stoichiometry. The highest uptake of carbon dioxide is observed on the sample with the highest ratio between rhombohedral and hexagonal delafossite phase. Highlights: Hydrothermal synthesis of CuFeO2 with delafossite structure. Characterization of bulk CuFeO2 by Raman spectroscopy and X-ray diffraction. Characterization of bulk CuFeO2 by light transmission to determine band gap. Characterization of the surface of CuFeO2 by X-ray photoelectron spectroscopy. quartz crystal microbalance is used to quantification the CO2 amount absorbed (wt%) by the compound.